CONFLICT MAPPING PIAGAM MADINAH (ANALISA LATAR BELAKANG SOSIOKULTURAL PIAGAM MADINAH) - Burhanuddin, Muhammad (JURNAL AL-IJTIMAIYYAH, 2019)
The Charter of Medina was able to unite of tribes in the Medina (Yastrib) to lived peacefully, pillars, and protect to each others. Peace is not be separated from the presence of conflicts before there. The reseacrher a formulation to tree problems. 1. Why the Charter of Medina was able use to unite the tribers or etnich are  fused in to one friday? 2. How is the concept of conflict mapping the Charter of Medina? 3.What is the main issue and supporting issue the formation of Chater of Medina?. This reseacrh use library reseacrh. The Method of this reseach is critical analysis description. The research results get that are; first  the Charter of Medina is a peace charter to unit the tribes that still ethnicity and often be in conflict as sosio-culture condition that has been in force in the community. Second the conflict mapping Charter of Medina could be the existence of the condition a  position of Muhammad and his folowers in Mecca. So the presence of closely related conflict mapping intern between tribes, tribes of Medina who positioned Muhammad as universal. Second the main issues in the Medina Charter; safety, power, and resource. The suppoting issues are; unity of the people, rule of law, islamic union, public protection, protection of minorities, and highest power in the law of Medina as stated in the articles of the Charter of Medina.Keywords: conflict, the Charter of Medina, conflict mapping, issues, and sociocultural.